2015
DOI: 10.1177/1098612x15581407
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency ultrasound of Peyer’s patches in the small intestine of young cats

Abstract: Presumed normal lymphatic tissue in the small intestinal submucosa can be seen with high-frequency ultrasound and is a common finding in young cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…In our study, in the ileal samples where this line was observed, there was no evidence of dilated lymphatic vessels or mucosal fibrosis histologically and only the enlarged submucosal lymphoid follicles (Peyer's patches) differed from the other intestinal samples lacking this hyperechoic thin mucosal line. Our finding is similar to a recent study in cats, reporting an asymmetrically positioned hypoechoic extra layer in the submucosa of the distal jejunum and ileum (separated from the mucosa by a thin hyperechoic line identical to the one observed in our study) using high‐frequency ultrasound, representing asymmetrically positioned normal lymphatic tissue (Peyer's patches) in the lamina propria and submucosa histologically . The difference of distribution of this line between our study (circumferential) and the aforementioned feline study may be due to the difference of distribution of the lymphoid tissue in these two species, more circumferential in the canine ileum and antimesenteric in cats .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, in the ileal samples where this line was observed, there was no evidence of dilated lymphatic vessels or mucosal fibrosis histologically and only the enlarged submucosal lymphoid follicles (Peyer's patches) differed from the other intestinal samples lacking this hyperechoic thin mucosal line. Our finding is similar to a recent study in cats, reporting an asymmetrically positioned hypoechoic extra layer in the submucosa of the distal jejunum and ileum (separated from the mucosa by a thin hyperechoic line identical to the one observed in our study) using high‐frequency ultrasound, representing asymmetrically positioned normal lymphatic tissue (Peyer's patches) in the lamina propria and submucosa histologically . The difference of distribution of this line between our study (circumferential) and the aforementioned feline study may be due to the difference of distribution of the lymphoid tissue in these two species, more circumferential in the canine ileum and antimesenteric in cats .…”
Section: Discussionsupporting
confidence: 90%
“…Our finding is similar to a recent study in cats, reporting an asymmetrically positioned hypoechoic extra layer in the submucosa of the distal jejunum and ileum (separated from the mucosa by a thin hyperechoic line identical to the one observed in our study) using high‐frequency ultrasound, representing asymmetrically positioned normal lymphatic tissue (Peyer's patches) in the lamina propria and submucosa histologically . The difference of distribution of this line between our study (circumferential) and the aforementioned feline study may be due to the difference of distribution of the lymphoid tissue in these two species, more circumferential in the canine ileum and antimesenteric in cats . In dogs, a total of 26–29 Peyer's patches are described, with two different types reported, depending on their location .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…An additional, asymmetrically positioned, hypoechoic layer of around 1 mm thickness within the submucosa of the feline distal jejunum and ileum is often visible when using high frequency ultrasound(Figure 8) 12. In some cats, the extra layer may have a lobulated appearance owing to the presence of multiple separate rounded hypoechoic structures located adjacent to each other.…”
mentioning
confidence: 99%